Comparative impacts of project-based learning and other strategies on creative thinking in STEAM education: A systematic literature review - Ahmad Ijlal Abdika; Arief Agoestanto; Scolastika Mariani; Sugiman Sugiman (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Creative thinking is the ability to generate and develop new ideas. It is considered a high-level thinking skill that plays a crucial role in the 21st century. According to the 2022 PISA results, the creative thinking skills of Indonesian students are categorized as low. The Project-Based Learning (PjBL) model, when integrated with the STEAM approach, offers a promising strategy to enhance creative thinking. This study aims to provide an overview of how various teaching strategies—particularly PjBL—compare to other approaches in fostering creative thinking through the STEAM framework, using a Systematic Literature Review. Following the PRISMA protocol, nine relevant articles were identified that addressed the research questions. The findings indicate that the PjBL-STEAM approach has a significantly more positive, profound, and sustainable impact on improving creative thinking skills across all educational levels compared to other pedagogical strategies. PjBL fosters creativity not only as an academic skill but also as a life competency, integrated with 21st-century social, emotional, and problem-solving abilities. This study offers direction for future research in evaluating effective learning models to enhance creative thinking.